Sebaran Penduduk yang Tidak Merata dan Dampaknya Bagi Kehidupan - Amanda Alicia; Mulia Sari; Ayuni Kartika (Lembaga Pengembangan Kinerja Dosen, 2024)
Uneven population distribution is a condition where the population in an area is not distributed evenly and regularly. Uneven population distribution can be seen between rural areas and urban areas. Factors that influence these conditions are geographical conditions, environmental conditions and economic development. Indonesia has a very large territory so it is difficult to evenly distribute the population. Uneven population distribution has positive and negative impacts on life. The positive impact is to encourage economic growth and improve infrastructure. The negative impact is social inequality, crime, and can trigger traffic jams.